Electronic Cigarettes in Maine: Health Effects, Marketing, Use, and Regulation - Harris, David; Lelli, Barbara; Mayberry, Sarah (Maine Policy Review, 2017)
Electronic cigarettes (e-cigarettes) are electronic nicotine-delivery systems (ENDS) that deliver a vapor of nicotine and other potentially dangerous chemicals to the user; nonusers are also exposed. Driven by a well-funded advertising campaign, use of e-cigarettes has increased in Maine until it now exceeds the use of combustible cigarettes among youth. In 2015, 14.5 percent of female high school students and 18.8 percent of male high school students in Maine reported current use of e-cigarettes. Maine laws and city ordinances restrict e-cigarette use in some places where combustible cigarettes are banned, but legislative gaps remain. Most Maine schools, colleges, and hospitals also ban e-cigarettes, but again gaps remain. This article explores the marketing and use of e-cigarettes nationwide and in Maine and proposes policies to restrict access and use, particularly by youth.
Keywords: smoking; electronic cigarettes; tobacco; nicotine